Exergy analysis of a circulating fluidized bed boiler cogeneration power plant - Gurturk, Mert; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2016)
In this study, energy and exergy analysis of a cogeneration power plant have been performed. The steam which is produced by the cogeneration power plant is used for salt production and most important part of the cogeneration power plant is the circulation fluidized bed boiler. Energy and exergy efficiency of the circulation fluidized bed boiler were found as 84.65% and 29.43%, respectively. Exergy destruction of the circulation fluidized bed boiler was calculated as 21789.39 kW and 85.89% of exergy destruction in the plant. The automation system of the cogeneration power plant is insufficient. Exergy efficiency of the plant was calculated as 20%. Also, some design parameters increasing energy losses were determined. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Exergy; Fluidized bed; Cogeneration; Power plant; Coal combustion